Response of primary and secondary rainforest flowers and fruits to a cyclone, and implications for plant‐servicing bats - Annette T. Scanlon; Sophie Petit; Marika Tuiwawa; Alivereti Naikatini (Global Change Biology, 2018)
The response of primary (PF) and secondary (SF) rainforests to cyclones has broad implications for servicing fauna and the resilience of forest functions. We collected fine‐scale data on the reproductive phenology of plant communities in Fijian PF and SF in 12 monthly surveys before and after Cyclone Tomas (2010). We generated a resource index from the reproductive loads of 2218 trees and 1150 non‐trees (>190 species) and trunk and stem diameter to assess patterns in resource abundance for nectarivores and frugivores (hereafter NF resources). We aimed to determine (i) whether species richness of NF resources differed between forests; (ii) the patterns of resilience of NF resources at community level in both forests after a cyclone; and (iii) the effect of response on NF resources for plant‐servicing bats (Pteropodidae). In 12 months preceding the cyclone, NF resources were greater in PF trees; non‐tree resources fluctuated and were greater in SF. Lower species richness of NF resources in SF indicated that fewer opportunities exist there for exploitation by a diverse fauna. More resources were available for bats in PF. In 12 months following the cyclone, PF flowers and fruits, and SF fruits specifically used by pteropodid bats decreased for trees. Non‐tree resources were especially susceptible to the cyclone. No universal pattern of decline was associated with the cyclone; instead, some NF resources declined and others were resilient or responded rapidly to a post‐cyclone environment. Both PF and SF demonstrated resilience at the community level via increased flower survival (PF) and rapid flower production (SF). Reduced species richness of NF resources in SF will compromise future resilience and response to disturbance, including for threatened pteropodid bat species. These findings are critical for long‐term management of forests, given predicted increases in cyclone frequency and intensity associated with anthropogenic climate change.